Antibody deficiency associated with gold treatment: natural history and management in 22 patients. Issue 9 (September 1996) - Snowden, N; Dietch, D M; Teh, L S; Hilton, R C; Haeney, M R
Abstract : OBJECTIVE: To perform a clinical and immunological study of patients with rheumatoid arthritis who develop subnormal serum immunoglobulins on gold treatment; to clarify the nature of the defect in antibody production and determine the natural history of this adverse reaction; to use this information to suggest guidelines for the detection, investigation, and management of this complication. METHODS: 22 patients who developed subnormal levels of one or more immunoglobulin isotypes while receiving gold treatment were recruited over a 10 year period from the practice of a single rheumatologist. Antibody production was assessed by measurement of total immunoglobulins and of specific antibody production against polysaccharide and protein antigens, with test immunisation if necessary. RESULTS: Two broad patterns of antibody deficiency were identified: (1) (n = 11) mild, affecting only one immunoglobulin isotype and with normal specific antibody production. These patients were in general able to continue gold without further deterioration in antibody production. (2) (n = 11) severe, affecting two or three immunoglobulin isotypes, with defective specific antibody production. Six patients developed significant infections and were treated with immunoglobulin. Gold was discontinued in all. Normal antibody production recovered in nine patients, and in all but one followed for more than one year. No relation was seen between duration/dose of gold and antibody deficiency. CONCLUSIONS: Gold-induced antibody deficiency may be more common than usually recognised. A spectrum of deficiency exists, with some patients developing infective complications. Antibody production should be monitored in patients on gold treatment.